Innovative factor and competitive performance of product modularity among manufacturing firm - Ibrahim, Amlus; Nasir, Siti Muyassarah; Zainol, Nor Raihani; Ramayah, T. (2010)
Innovation can be defines as the introduction of new things, ideas or ways of doing something that has been introduced or discovered. Innovation has recently been regarded as an important factor for firms to develop and maintain their competitive edge.It is important for firms to identify the key factors for promoting a firm’s product and process innovation. These factors include entrepreneurship paradigm, business strategy,organizational learning and knowledge management.Modularity come from the word of module.According to Baldwin et al., (2000), module can be define as the structural elements that match among themselves but do not suitable connected with the elements that outside from their units. From here, we can said that module is a self-contained subassembly and can connects to other modules which have same interfaces.Modular can contain a large range of valueadded and complexity ranging from simple which is disposable modules.The use of this modules can facilitate the design of production systems as well as customized configuration of finished product. competitive performance relates to the outcomes of cost, quality, flexibility, and cycle time.This study focuses on the effects of product modularity on various dimensions of competitive performance; which are cost, quality, flexibility, and cycle time.The objective of this study is to examine the relationship between competitive performance of product modularity and innovative factor influencing its adoption among manufacturing firms in Northern region of Malaysia.Thus, there are six research questions to be answered in this study, what are the role and the impact of modularization, what is the effect of product modularity on various dimensions of competitive performance which is cost, quality, flexibility and cycle time